The Paradox of the Sovereignty of the Constitutional Court in the Context of Protecting Democracy and the Constitution in Indonesia - Mutiasi, Novia; Kristanto, Budi (Al-'Adl, 2025)
The Constitutional Court is a state institution that was born after the Constitutional Court reform in 1999. Through amendments to the 1945 Constitution, the Constitutional Court is authorized to test laws (statutes) against the Constitution. In addition, there are other powers to protect human rights relating to the constitutional rights of citizens. As a state institution that has the authority, among others, of the Constitutional Court, as the highest interpreter of the constitution in addition to realizing democratic government, the Constitutional Court acts as a guardian of democracy, protection of citizens' constitutional rights and protection of human rights, this research uses a mapping tool in the form of a VOSViewer application that can present and present specific information about the research conducted.